2022
DOI: 10.12659/msm.938578
|View full text |Cite
|
Sign up to set email alerts
|

Factors for In-Hospital Mortality in 145 Male Patients with Fournier’s Gangrene: A 10-Year Observational Study from a Single Tertiary Referral Center in Indonesia

Abstract: Background Fournier’s gangrene (FG) is a potentially fatal necrotizing infection. Due to the rapid progression of the disease, the fatality rate remains high despite advances in therapy. This 10-year observational study from a single tertiary referral center in Indonesia aimed to identify the risk factors for in-hospital mortality from 145 male patients diagnosed with FG. Material/Methods This retrospective cohort study was conducted at one of Indonesia’s largest tertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…In our study, the need for ICU admission was associated with non-survival, and our result was similar to a study by Azmi et al (8). In contrast, in the study by Yilmazlar et al, survivors stayed in the hospital significantly longer than non-survivors (24).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, the need for ICU admission was associated with non-survival, and our result was similar to a study by Azmi et al (8). In contrast, in the study by Yilmazlar et al, survivors stayed in the hospital significantly longer than non-survivors (24).…”
Section: Discussionsupporting
confidence: 90%
“…FG is a life-threatening condition that involves necrotizing fasciitis in the genitourinary areas and the perineum. It is typically a polymicrobial infection caused by anaerobic and facultative aerobic bacteria (8). The rapid progression of FG is linked to impaired cellular immunity, which permits suppurative bacterial infection, and the synergetic polymicrobial nature, which causes a substantial release of bacterial toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Fournier's gangrene is an extremely rare but fatal illness that affects delicate tissues of the perianal and perineal areas [ 15 ]. Many studies have shown that its overall incidence is much lower in women than in male patients [ 16 , 17 ]. Patients with Fournier's gangrene have a high mortality rate of more than 25 % [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Azmi et al 20 noted diabetes mellitus as a comorbidity and Clostridium perfringens as the cause of FG as the independent risk factors for mortality in their study using multivariate regression analysis.…”
Section: Risk Stratification and Prognosismentioning
confidence: 96%